The usefulness of preoperative bile cultures for hepatectomy with biliary reconstruction - Kenta Makino; Takamichi Ishii; Tomoaki Yoh; Satoshi Ogiso; Ken Fukumitsu; Satoru Seo; Kojiro Taura; Etsuro Hatano (Heliyon, 2022)
Background: Infectious complications can cause lethal liver failure after hepatectomy with biliary reconstruction. This study assessed the increased risk for postoperative infectious complications in patients who underwent hepatectomy with biliary reconstruction and explored the possibility of predicting pathogenic microorganisms causing postoperative infectious complications based on preoperative monitoring of bile cultures. Methods: This study involved 310 patients who received major hepatectomy with or without biliary reconstruction at our institution between January 2010 and December 2019. The relationship between the microorganisms detected through perioperative monitoring of bile culture and those in the postoperative infectious foci was examined. Results: Forty-nine patients underwent major hepatectomy with biliary reconstruction, and 261 received hepatectomy without biliary reconstruction. The multivariate analysis revealed hepatectomy with biliary reconstruction to be associated with an increased risk of postoperative infectious complications (odds ratio: 22.9, 95% confidence interval: 5.2–164.3) compared to hepatectomy without biliary reconstruction. In the patients with biliary reconstruction, the concordance rates between the microorganisms detected in the postoperative infectious foci and those in preoperative bile cultures were as follows: incisional surgical site infection (44.4%), organ/space surgical site infection (52.9%), bacteremia (47.1%), and pneumonia (16.7%); the concordance rates were high, and the risk of infection increased over time. Conclusions: Biliary reconstruction is a significant risk factor for postoperative infectious complications, and preoperative bile cultures may aid in prophylactic and therapeutic antimicrobial agent selection.